THE EQUIVALENT OF THE JAPANESE VERBS SONAERU, SASHIAGERU, AND SAZUKERU INTO INDONESIAN - Dian Aryani, Made Ratna; Anggraeny, Renny (Lire Journal (Journal of Linguistics and Literature), 2021)
This research focuses on the verb equivalent of 'giving' Japanese into Indonesian. Japanese and Indonesian have different expressions of the 'giving' verb, both syntactically and pragmatically. The method used in this study is a qualitative descriptive method. In this study, the theory used is semantic theory from Chaer which states lexical meaning and grammatical meaning. The pragmatic theory used in this study is the contextual theory from Pateda. The data source of this study uses data from the Japanese corpus, namely www.kotonoha.gr.jp/shonagon/.The results of this study indicate that syntactically the verbs of sonaeru, sashiageru and sazukeru each have a different structure in Japanese. This is related to the emergence of function markers in arguments in Japanese sentence structures. And semantically, the emergence of the function of the marker affects the meaning and use of the vocabulary